2021
DOI: 10.1103/physreve.104.054409
|View full text |Cite
|
Sign up to set email alerts
|

Volume segregation programming in a nematode's early embryogenesis

Abstract: Nematode species are well-known for their invariant cell lineage pattern, including reproducible division timing, volume segregation, fate specification and migration trajectory for each and every cell during embryonic development. Here, we study the fundamental principle optimizing cell lineage pattern with Caenorhabditis elegans. Combining previous knowledge about the fate specification induced by asymmetric division and the anti-correlation between cell cycle length and cell volume, we propose a model to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…The discrepancy may be related to the definition of symmetry (see Discussion). A recent study that performed quantitative analysis of cell volume showed that divisions of EMS and Ca were symmetric (Guan et al, 2021), which is consistent with our results. Altogether, our results showed agreement with the previous study in 93% (25/27) of divisions.…”
Section: Reproduction and Extension Of A Previous Studysupporting
confidence: 93%
“…The discrepancy may be related to the definition of symmetry (see Discussion). A recent study that performed quantitative analysis of cell volume showed that divisions of EMS and Ca were symmetric (Guan et al, 2021), which is consistent with our results. Altogether, our results showed agreement with the previous study in 93% (25/27) of divisions.…”
Section: Reproduction and Extension Of A Previous Studysupporting
confidence: 93%
“…For instance, in modeling cell positioning, physical simulations show why the timing and orientation of cell division and cell–cell adhesion are programmed as they are in vivo [57] , [90] , [195] , [196] . In mechanical terms, this programming ensures the precise and robust realization of the developmental path of embryonic morphology [19] , [20] , [75] , [89] , [91] , [92] , [93] , [94] , [95] , [197] , [209] , [212] . Physical modeling also provides answers to the perennial question of why and how the C. elegans developmental procedure is so reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the severely deformed cell shape that comprises filopodia and lamellipodia structures can mediate the movement of cells, such as ABpl during the left–right asymmetric chiral morphogenesis from the 7- to 8-cell stages [75] , [76] , [87] , [88] . Second, cell volume, which is determined by the symmetric or asymmetric division of a mother cell, influences the nucleus-to-cytoplasm ratio and the molecular contents allocated to the daughter cell, which regulates this cell’s fate, cycle length and the robustness of its arrangement [89] , [90] , [91] , [92] . Third, cell–cell contact serves as a physical basis for signal transduction between specific cell pairs that regulates the signal-receiving cell’s orientation during division (e.g., Wnt signaling from C to ABar at the 8-cell stage) and fate specification (e.g., Notch signaling from MS to ABalp and ABara instead of to ABala and ABarp at the 12-cell stage) [22] , [23] , [24] , [93] .…”
Section: Cellular-resolution Studies Of Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…J. , 2023]? About the downstream, as the cell size asymmetry is accurately programmed with a limited tolerance for successful embryogenesis and is critical for cell cycle length asymmetry as well as consequential cell arrangement progression [Jankele et al, eLife , 2021; Guan et al, Phys. Rev.…”
Section: Introductionmentioning
confidence: 99%